2017
DOI: 10.2147/ott.s150139
|View full text |Cite
|
Sign up to set email alerts
|

PBX3 is associated with proliferation and poor prognosis in patients with cervical cancer

Abstract: Pre-B-cell leukemia homeobox 3 (PBX3) is upregulated in various malignancies; however, the role of PBX3 in cervical cancer (CC) is unknown. The purpose of this study was to explore the expression characteristics, clinicopathological significance, and molecular biological function of PBX3 in CC. The expression levels of PBX3 were analyzed in CC cell lines and tumor specimens by real-time polymerase chain reaction (RT-PCR), Western blotting, and immunohistochemical staining. The clinicopathological characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…PBX3 is highly expressed in a variety of cancer tissues, such as prostate and cervical cancer [14,16]. Han et al demonstrated that PBX3 expression is a critical determinant for maintaining the characteristics of tumorinitiating cells in hepatocellular carcinoma [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBX3 is highly expressed in a variety of cancer tissues, such as prostate and cervical cancer [14,16]. Han et al demonstrated that PBX3 expression is a critical determinant for maintaining the characteristics of tumorinitiating cells in hepatocellular carcinoma [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that PBX3 is a critical regulatory protein of the epithelialmesenchymal transition (EMT) network in colorectal cancer [13]. Dysregulation of PBX3 expression has been observed in many cancer types, such as prostate, gastric, cervical, and liver cancer [14][15][16][17]. Nonetheless, the expression and function of PBX3 in LSCC are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In cervical cancer, PBX3 overexpression promotes proliferation through the AKT pathway, and high levels of expression in primary tumors are associated with a poor prognosis [57], and, as with the other cancers described above, PBX3 expression is suppressed by an miR, miR-526b, preventing cells from undergoing EMT [35].…”
Section: Other Cancersmentioning
confidence: 97%
“…Based on the above, it is becoming clear that PBX3 interacts principally with the MAPK, AKT, and WNT signaling pathways (Figure 1). PBX3 was shown to increase signaling through MEK/ERK in several studies [18,57,58], although to date the only component of the pathway shown to be directly upregulated by PBX3 is the tyrosine kinase receptor Flt3 [41]. Activation of this pathway represents a positive feedback loop in which increased expression of the Myc transcription factor activates LIN28 expression, which in turn inhibits biogenesis of miR-let-7b, an miR that blocks PBX3 expression post-transcriptionally [18].…”
Section: Pbx3-regulated Pathways In Cancermentioning
confidence: 99%
“…The overexpression of NOTCH3 is correlated with the overexpression of Jagged-1 and Pbx1b in cervical SCCs, yet there is no established relationship between Pbx1b overexpression and patient survival (Yeasmin et al, 2010). PBX3 is overexpressed in the cytoplasm of cervical cancer cells and tissues and its expression is related to poor prognosis, tumor diameter, pathological grade, clinical stage lymph node metastasis, invasion depth, and vascular invasion (Li et al, 2017). The function of PBX3 is likely controlled by the AKT signaling pathway in cervical cancer (Li et al, 2017).…”
Section: Gynecologic Cancersmentioning
confidence: 99%